2019
DOI: 10.1109/tmag.2019.2933701
|View full text |Cite
|
Sign up to set email alerts
|

A Planar Generator for a Wave Energy Converter

Abstract: This paper presents a permanent magnet planar translational generator which is able to exploit multiple modes of sea wave energy extraction. Linear electrical generators have recently been studied for the exploitation of sea wave energy, but, to the best of our knowledge, no synchronous planar translational generator has been proposed. In this paper, to maximise the energy extraction, we have considered all the potential modes of motion due to wave excitation and included them within the mathematical model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A review of the current WEC technology is reported in [7]. This stage converts the mechanical energy contained in the wave motion into a more usable mechanical energy; the coupling device introduces additional losses, weakness in the reliability of the system and additional maintenance requirements [10].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the current WEC technology is reported in [7]. This stage converts the mechanical energy contained in the wave motion into a more usable mechanical energy; the coupling device introduces additional losses, weakness in the reliability of the system and additional maintenance requirements [10].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [5] proposed a direct-drive WEC using an outer-permanent magnet linear generator that can increase the power density and relative movement distance to improve energy conversion efficiency. Wang et al [6] proposed a planar generator for a WEC system that can use rolling and pitching motion to produce electrical power.…”
Section: Introductionmentioning
confidence: 99%
“…The later class of converters can produce shear stress up to 10 times more compared to that of those in traditional electrical generators with very low loss [15]. An optimized planar linear generator is proposed in [16], which is capable of utilizing several modes of OWE conversion. Optimal design of the generator is developed based on parameters of the electrical equivalent circuit and the properties of oceanic wave.…”
Section: Introductionmentioning
confidence: 99%